การติดตามการเปลี่ยนแปลงสัณฐานวิทยาชายหาดจากหาดแม่รำพึง จังหวัดระยอง - กานต์กวี นิลสิทธิกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
Mae Rampung beach, Rayong province is one of famous and popular tourist places due to straight and clean beach with small rocky headland in the middle part. Under seawater rocks expose during low tide and submerge during high tide. According to Department of Marine and Coastal Resources reported in 2015, Mae Rampung beach was in moderate erosion rate (1-5 m/year). This study is aimed to monitor long- and short-terms morphological changes and coastal sediments balance in order to analyze possible factors that may affect the risk of tourism activity by two approaches. Firstly, analysis in satellite images was carried out in order to monitor horizontal spatial changes by measurement of shoreline moving rates from year 2003 to 2016. This longterm monitored for 13 years. Secondly, short-term beach profiling was set up to monitor sediments balance in the early, during and after northeast monsoon. The study area was divided into 3 coastal sectors: north, middle and south. As a result, comparison in shoreline position from satellite images (taken from 2003-2016) reveals that the shoreline in Mae Rampung beach is stable because the trend and morphology of the high tide shorelines shows similar pattern. There is no significant difference. Physical factors that may causes of dangerous in this beach include the difference in slope gradient and non-irregular beach face due to submerged granite leading to the occurrence of unusual current during high tide.